ANALISIS STRATEGI PEMASARAN CV KARUNIA MAKMUR PERSADA ( KMP ) DENGAN METODE SWOT - Yusnia Sinambela; Darnianti Darnianti; Natanael Panjaitan (Universitas Quality, 2018)
This study aims to analyze strategies through strengths, weaknesses, opportunities, threats, to compile IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Summary Analysis) and to find out marketing strategies in CV KMP after being analyzed by SWOT (Strengths, Weaknesses, Opportunities , Threaths). The conditions in the company in the face of fierce competition are marked by the increase of companies in the same field. This study identifies internal factors and external factors of the company. Data was collected through observation and division of questionnaires to workers totaling 20 people. The results of the study show the following values: (1) The results of IFAS analysis are 0.55 that the strategic position is in the average position, where the strongest factor in the company's internal is the guaranteed product quality and the building is the property. (2) EFAS analysis results obtained a score of 0.14 where this position is a middle position from the company's external factors, meaning that there are still many companies to optimize opportunities to minimize existing threats.